Effects of plyometric versus resistance training on sprint and skill performance in young soccer players - Haghighi, A.; Moghadasi, M.; Nikseresht, A.; Torkfar, A.; Haghighi, M. (European Journal of Experimental Biology, 2012)
The aim of this study was to investigate the effect of plyometric versus resistance training (PT vs. RT) on sprint and skill performance in young soccer players. Thirty elite soccer players participated in this study as the subject. The subjects were randomly assigned to PT group (n=10, age: 19.1 ± 1.7 years), RT group (n=10, age: 18.0± 0.81) or control group (n=10, age: 18.8 ± 1.5 years). The PT group performed 8 weeks lower extremities PT besides the soccer team training. The RT consisted of 2-4 sets of weight training for 4 stations and at an intensity corresponding to 60-90% of 1-RM in each station by 6-12 repetitions besides the soccer team training. The control group performed only the soccer team training during the study. The results showed that the time of sprint running test and dribbling improve after PT and RT (P<0.05). For accuracy of shooting no significant change was observed after 8 weeks PT and RT. In conclusion, although the time of sprint running test and dribbling improve after PT and RT, these training have not effective to improve accuracy of shooting in young soccer players.